Gender Stereotypes from A Management Perspective: A Literature Review - Juniar Alisa; Ela Laela; Rita Nurjanah (Pusat Studi Gender Universitas Jember, 2024)
Gender stereotypes are often assumed to limit the capacity to develop and make decisions. Gender stereotypes are also considered the main reason for the glass ceiling and maze effect. This study uses a literature review to synthesize gender stereotype research. A literature search was carried out with publication years limited from 2003 to 2023. The literature analyzed was collected from Scopus-indexed journals with the ScienceDirect, Springer, Wiley Online Library, and Emerald Insight databases. This research synthesizes and analyzes 40 relevant articles focusing on discussing gender stereotypes. Based on the analysis results, men and women have different stereotypes. Men are considered superior in their characteristics. However, while gender stereotypes still hamper women, there are reasons to remain optimistic. When women are the targets of gender bias, it is not just them but the organizations where they work and society as a whole who suffer. Conclusions with limitations and recommendations for further research are included in the article.